PATTERN OF SKIN DISEASES IN ABBAS INSTITUTE OF MEDICAL SCIENCES, MUZAFFARABAD - Fasih, Sadaf; Arif, Asad Bilal; Younas, Sana (Pakistan Journal of Physiology, 2017)
Background: The pattern of skin diseases in an area is governed by a number of factors like climate, geography, personnel hygiene, overcrowding, nutritional and socioeconomic status, educational back ground and genetics. The objective of this study was to analyze the pattern of skin disorders in patients attending the Dermatology Outpatient Department of AIMS, Muzaffarabad. Methods: This was a hospital based descriptive study carried out at Dermatology Outpatient Department of AIMS, Muzaffarabad from 1st January, 2017 to 31st March, 2017. All patients presenting at the Dermatology Department OPD during this period were included after informed consent. The diseases were categorized as ten aetiological/pathological groups and frequencies of different disease groups were calculated and tabulated as MeanÂ±SD using SPSS-21. Results: A total of 2,635 patients were included in the study. Over all the infections of the skin and subcutaneous tissue were the most common (1,043, 39.4%), followed by eczemas (538, 21%), disorders of glands (351, 13.3%), pigmentary disorders (263, 10%), and all other disorders of skin and subcutaneous tissue (440, 16.3%) in the total population of patients. Conclusion: Communicable skin diseases are prevalent skin disorders seen in Muzaffarabad and suburbs. Appropriate health services and training of health staff and public awareness is required to overcome this situation. Pak J Physiol 2017;13(4):26â€“9